Strategic Leadership and Sustainability Literature Review - Tatang Sutarman; Supardi Tahir (Dinasti Publisher, 2026)
The relationship between leadership and sustainability has emerged as a critical area of scholarly inquiry, reflecting the urgent need for organizations to address environmental challenges while maintaining economic viability and social responsibility. This comprehensive review synthesizes evidence from 30 highly relevant empirical studies and reviews published primarily between 2016 and 2026, examining how leadership styles, mechanisms, and practices influence organizational and environmental sustainability outcomes. The evidence demonstrates that specific leadership styles—particularly transformational, green transformational, green servant, and sustainable leadership—positively predict sustainability performance through mechanisms including vision articulation, role modeling, green human resource management (HRM) alignment, employee empowerment, and knowledge diffusion. Outcomes span green innovation, environmental performance, employee well-being, and competitive advantage. Theoretical frameworks employed include the Full-Range Leadership Model, AMO (Ability-Motivation-Opportunity) theory, and CSR governance models. Despite promising findings, significant gaps persist in conceptual clarity, methodological rigor, geographic diversity, and measurement standardization. This review provides a structured synthesis for researchers and practitioners seeking to understand and leverage leadership for sustainability.